Characterization of storage and distribution logistics in the Metropolitan Health Region’s warehouses, El Salvador, 2024-2025 - Martínez de Martínez, Ana Guadalupe; Jorna Calixto, Ana Rosa; Pria Barros, María del Carmen (Horizonte Sanitario, 2025)
Objective: To characterize the environmental, organizational, and operational conditions under which storage and distribution operations are carried out in the Warehouses of the Metropolitan Health Region. Materials and Methods: A descriptive observational cross-sectional, field study with a mixed-methods approach was conducted. Data collection was based on direct participatory observation of processes performed by administrative and operational staff during user service, using a structured observation guide to systematize data for analysis. Results: It was found that medical supplies and equipment are stored under inadequate conditions, marked by a lack of control and stability in temperature and humidity. Additionally, there is no systematic method for prioritizing supplies based on expiration dates. The physical space of the warehouses is insufficient, and the internal product distribution hinders agile and safe access to the supplies. Furthermore, there is an absence of regular supervision of storage and dispatch operations, limiting process efficiency and control. Conclusion: The environmental, organizational, and operational conditions of the regional warehouses were characterized, revealing significant deficiencies in the storage and distribution logistics system. These conditions reflect a logistics system that does not incorporate Good Storage Practices, negatively impacting the efficiency and quality of service provided to users. Therefore, improvements are necessary to ensure environmental, organizational, and operational standards that optimize management and guarantee the availability and quality of supplies. Keywords: Logistics, Drug Storage, Drugs, Good Storage and Distribution Practices.